Religiusitas, Spiritualitas, Dan Kesehatan Mental : Meta Analisis - Hepi Wahyuningsih (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2008)
A meta-analysis was performed in an attempt to clarify the proposed relationship between religiosity/spirituality and mental health. Specific focus was given to the issue of definition, measurement, namely, whether differences in researchers conceptualizations of religiosity/spirituality and mental health could account for the various contradictory findings.Analysis of 20 studies conducted during 6 past years revealed that the definitions of religiosity/spirituality and mental health utilized by researchers were indeed associated with different type and strengths of the correlations between religiosity/spirituality (r = 0,345), non-organizational religiosity (r = 0,445), intrinsic religiosity (r = 0,227), multidimensional religiosity (r = 0,253), spirituality r = 0,470), and positive mental health. There are negative correlation among organizational religiosity (r = -0,012), non-organizational religiosity (r = -0,188), intrinsic religiosity (r = -0,212), multidimensional religiosity ( r = -0,130), spirituality (r = - 0,046), and negative mental health. Key words     : meta-analysis, religiosity, spirituality, mental health..